2015
DOI: 10.1007/s00103-015-2288-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotikaeintrag in das urbane Abwasser

Abstract: Antibiotics are essential for the successful treatment of bacterial infections. Recently, the increasing number of resistant bacteria and the occurrence of residues of antibiotics in the environment has become the focus of scientific interest. The aim of the cooperative project ANTI-Resist was to investigate the release of antibiotics and the occurrence and distribution of antibiotic resistance in the urban waste water system of the city of Dresden.This article presents the main results of the secondary data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Comparable results have been found for carbamazepine, which represented another pharmaceutical substance with frequent prescription in Germany and high daily defined dose of 1.0 g (Ludwig et al 2021 ) (Federal Institute for Drugs and Medical Devices, Germany). Prescription data of the statutory health insurance AOK Plus, which represent around 41% of outpatients in Free State of Saxony, Germany (Timpel et al 2016 ), showed consistently high prescriptions of gabapentin and carbamazepine in catchments of investigated WWTPs in 2020 and 2021 (unpublished prescription data in cooperation with U. Maywald, AOK Plus, Dresden, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results have been found for carbamazepine, which represented another pharmaceutical substance with frequent prescription in Germany and high daily defined dose of 1.0 g (Ludwig et al 2021 ) (Federal Institute for Drugs and Medical Devices, Germany). Prescription data of the statutory health insurance AOK Plus, which represent around 41% of outpatients in Free State of Saxony, Germany (Timpel et al 2016 ), showed consistently high prescriptions of gabapentin and carbamazepine in catchments of investigated WWTPs in 2020 and 2021 (unpublished prescription data in cooperation with U. Maywald, AOK Plus, Dresden, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results have been found for carbamazepine, which represented another pharmaceutical substance with frequent prescription in Germany and high daily de ned dose of 1.0 g (Ludwig WD 2021), (Federal Institute for Drugs and Medical Devices, Germany). Prescription data of the statutory health insurance AOK Plus, which represent around 41% of outpatients in Free State of Saxony, Germany (Timpel, Gurke et al 2016), showed consistently high prescriptions of gabapentin and carbamazepine in catchments of investigated WWTPs in 2020 and 2021 (prescription data in cooperation with U. Maywald, AOK Plus, Dresden, Germany).…”
Section: Study 2 -Establishment Of Marker Substancesmentioning
confidence: 99%